Analysis of User Satisfaction with Activity Based Components at Caldera Adventure : Rafting & Resort Sukabumi: Analisis Kepuasan Pengguna Terhadap Activity Based Component di Caldera Adventure : Rafting & Resort Sukabumi - Batubara, Rima Pratiwi; Setiawan, Aditya Sugih; Da Venus, Cecilia (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
As global mobility increases and traveler preferences change, demand for unique and attractive accommodation is also growing rapidly. Accommodations specifically designed to provide an unforgettable holiday experience have become a focus of attention in the industry. Resorts are not only places to stay, but also tourist destinations in their own right, offering a variety of facilities and activities that attract tourists. The research in this journal aims to find out about one of the components in the assessment in the field of hospitality (hospitality assessment), namely the basic activities of the resort (activity based component). The research method used was descriptive qualitative, with Caldera Adventure: Rafting & Resort as the research location. Data was obtained through interviews, documentation and observation. The assessment indicators are based on resort user activity components based on Brey et al., (2008). The research results show that this resort offers family services, indoor and outdoor recreation, services related to well-being, a variety of activities for everyone, and entertainment activities. Increasing the variety of services and activities to attract more visitors and expand the customer base. It is hoped that this article can be used as a reference to increase the attractiveness of the resort so as to provide a richer staying experience for visitors and expand its positive impact on local tourism.